Pathological changes in the heart under the use of psychostimulants - S. V. Kozlov; K. М. Suloiev; V. V Koldunov; Yu. V. Kozlova; Sh. M. Mamedov (Zaporozhye State Medical University, 2019)
The aim of the work is to study pathomorphological changes in the heart in cases of death under the use of phenylalkylamine derivatives. Materials and methods. 58 forensic studies of people who died of poisoning with drugs during the period 2015-2017 in the Dnipropetrovsk region were done. All the deceased were men aged 28.8 ± 6.7 years. As a control, the hearts of 15 people aged 21-36 years who died due to external causes not related to the effects of narcotics were examined. All the deceased were men aged 28.1 ± 6.2 years. In all cases, the analysis of the circumstances, results of autopsy, forensic-histological, forensic toxicological and flame photometric studies was carried out. Results. Morphometric analysis revealed no significant changes in linear-weight characteristics of hearts in the deceased group compared to the control group. Mean K and Na levels in the samples corresponded to 172.4 ± 15.6 mg% and 125.5 ± 9.4 mg% respectively. K/Na ratio of the myocardium ranged from 0.94 to 1.85. In each investigated heart of the deceased due to amphetamine and methamphetamine use, significant changes in K/Na balance were detected, and the number of heart divisions, where the K/Na ratio was less than 2, ranged from 1 to 6. From data of analysis of microscopic changes of myocardium of the deceased, who used the derivatives of phenylalkylamine (amphetamine, metamphetamine) during of life, the complex of microscopic signs was set as intracellular changes (vacuolisation) from the side of cardiomyocytes, diffuse focal areas of perivascular and interstitial cardiosclerosis, in combination with focal myocytolisis and hypertrophy of cardiomyocytes without the signs of injury of coronal vessels. Conclusions. The study of the hearts of the deceased who used phenylalkylamine derivatives, characteristic pathological changes at the tissue (a complex of characteristic microscopic signs) and molecular (violation of potassium-sodium equilibrium) levels were detected, indicating the development of acute cardiac dysfunction.